We are a Fantasia: Violence, Belonging, and Potentiality in Transgender Latina Sexual Economies - Bolivar, Andrea (2018)
This dissertation ethnographically centers the lives of sex working transgender Latinas in Chicagoland. Based on 14 months of research collected between June 2015 and August 2016, I introduce fantasia as a racialized queer analytic to illustrate the unique ways in which transgender Latinas are objectified, racialized, and dehumanized in sexual economies of labor and in U.S. nation more broadly. Fantasia conveys trans Latinas' sexual otherness on account of their race and gender. They are imagined as hypersexual because they are Latinas, and fetishized because they are transgender women. Fantasia also indexes their ephemeral presence--they are always at risk of disappearing on account of their race and gender, and the ways in which the two come together. Furthermore, fantasia draws attention to the phantasmal: the long histories of racialized and gendered violence and exploitation that are embedded into trans women's bodies and linger in the present. Yet, it also reveals potentiality. I ethnographically demonstrate how the women creatively use their bodies to survive and at times thrive, by engaging in resistant forms of labor, kinship, and space-making. This timely work answers calls for more attention to transgender people of color, while bringing together feminist anthropology of sex work, Latinx Anthropology, and Queer Anthropology